Portuguese cities' happiness - Diana Jesus; Marta Pais; Inês Lencastre; Regina Salvador; Paulo Reis; Letícia Lopes (European Regional Science Association (ERSA), 2015)
Happiness is an aspiration of every human being, and can also be a measure of social progress. Yet can one say that citizens are happy? If they are not, what if anything can be done about it? (Helliwell, Layard, & Sachs, 2013, p. 3) Understanding cities and citizenship has become a common place in today?s regional and urban policies. To be able to quantify - and understand - concepts such as urban quality of living, wellbeing and happiness is an urban planning major tool. But how does one measure an abstract concept such as happiness and how does one eventually use this knowledge in to plan and build our cities? According to much of the debate over happiness, the wellbeing or life quality have been centered on the role of income even if human capital levels play an important role in the happiness of cities too. (Florida, Mellander, & Rentfrow, 2013, p. 614) Therefore, to know what happiness is and what a happy city means it is necessary to plan a high quality city for all citizens. This paper seeks to enlighten how happy the Portuguese cities are and how this happiness is related to structural, social or economics features. As happiness is hard to define and is composed by several and common factors (life quality, economic, housing, demographic, education, mobility, environment or geographic criteria) it is necessary to grasp its comprehension. Hence, twenty Portuguese cities were selected and analyzed using twenty variables that influence happiness, both according to literature and to empirical evidence. The Portuguese Life Quality Index (PLQI) - set by DECO and results from 21 Portuguese cities 2011 data - , was used as the dependent variable, a major proxy of wellbeing and happiness. The independent variables were collected from several statistical sources (2009-2013). Statistical analysis was first conducted using the correlation coefficient to estimate interdependence between the life quality index and other variables. In second place, multiple regression analysis was used to identify which of the pre-selected independent variables impacts happiness the most. Correlation findings shows, opposite and surprising results taking into account literature previews and other countries? empirical, results. A negative and significant correlation (-0.514) between PLQI and wages levels suggests that it is in the low wages cities that people are happier. This and other unexpected results mean that further research is needed. Regressions findings confirm that housing variables explain about 44% of the variation in the PLQI. Overall, defining and measuring happiness is not an easy task. This paper results confirm that happiness is not only related with social, economic or structural features, but also comprehends a fourth dimension, cultural, environmental or even individual one.
Keywords: 330; Happiness index; Portugal; Cities